Optimization of Processing Parameters of Medium Density Fiberboard Using Response Surface Methodology for Multiwalled Carbon Nanotubes as a Nanofiller - Kumar, Anuj; Sharma, K. V.; Gupta, Arun; Tywoniak, Jan; Hajek, Petr (Springer Berlin Heidelberg, 2017)
In the present work, medium density fiberboard (MDF) panels were produced using multiwalled carbon nanotubes (MWCNT) reinforced urea formaldehyde resin. Response surface methodology was employed to optimize the relationship between the three variables, viz. pressing time, percentage of UF resin and percentage of MWCNT, used in the fabrication of MDF, and the influence of variables on the internal bonding (IB) and modulus of rupture (MOR) was studied. The optimum conditions based on the IB strength were determined as 8.18 % of UF resin, pressing time of 232 s, and MWCNT of 3.5 %. Similarly, the optimized conditions for MOR are also reported in this paper.